Downregulation of DNAJC12 Expression Predicts Worse Survival for ER-Positive Breast Cancer Patients - Pedro Henrique Fernandes Gatti; Flavia Regina Rotea Mangone; Ana Carolina Pavanelli; Suely Nonogaki; Cynthia Aparecida Bueno de Toledo Osorio; Vera Luiza Capelozzi; Maria Aparecida Nagai (Biomarker Insights)
Background: DNAJC12 (DnaJ heat shock protein family (Hsp40) member C12) encodes a member of the molecular chaperone Hsp40/DnaJ family, which are important protein folding and proteostasis regulators. Its role as a biomarker has been studied for a limited number of cancer types. Objectives: Here, we sought to investigate the potential of DNAJC12 mRNA and protein expression as a prognostic and predictive biomarker for breast cancer (BC). Methods: Using in silico analysis and data from immunohistochemistry analysis (IHC) of 292 samples from patients with primary BC, we determined the expression pattern and prognostic value of DNAJC12 mRNA and protein expression. Results: From online publicly available data, we were able to identify the transcripts of DNAJC12 as differentially expressed in patients with different clinicopathological characteristics, such as ER status ( P  < .001), PR status ( P  < .001), HER2 status ( P  < .010) and molecular subtype ( P  ⩽ .001). We also found DNAJC12 to be a potential prognostic predictor for overall survival, disease-free survival, and responsiveness to treatment; a low DNAJC12 mRNA expression is commonly associated with a worse prognosis. Using IHC analysis, we showed that low DNAJC12 protein-level expression is also associated with a worse prognosis in patients with all subtypes of BC and patients with Luminal BC, and its expression is significantly different between patients with different tumor size classifications (T1/T2 vs T3/T4; P  = .013) or with different lymph node involvement (N0 vs N+; P  = .005). Conclusion: Our findings suggested a potential role for DNAJC12 as a prognostic and predictive biomarker for BC.